Obstructive jaundice resulting from Hodgkin’s disease - Estapé, Gonzalo; Altieri, Carlos; Torterolo, Edgardo; Portos, Ruben; Medina, Raúl; Pizzarrossa, Carlos (Cirugía del Uruguay, 1979)
The author presents the first case found in Uruguayan medica! literature of obstructive jaundice resulting from infiltration of hepatic pedicle by a mass of fibrous tissue of the type found in Hodgkin's disease.